2008
DOI: 10.1016/j.bbr.2007.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin II increases spontaneous parental behavior in prairie voles (Microtus ochrogaster)

Abstract: Stress and anxiety play a role in many psychological processes including social behavior. The present study examines the effects of urocortin II (UCN II) on spontaneous parental behavior in adult prairie voles (Microtus ochrogaster). UCN II was found to increase passive parental behavior in voles while not affecting any stress-related measures. Delineating the mechanism of this change will aid in our understanding of the regulation of parenting. Keywordscorticotrophin-releasing hormone; urocortin I, II, and II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Nevertheless, it has been demonstrated that UCN1 and UCN3 modulate maternal behavior via CRH-R2 in the lateral septum D'Anna and Gammie, 2009), and accordingly, CRH-R2 knock-out mice exhibit impaired maternal defense of their offspring . Along these lines, UCN2 increases spontaneous parental behavior in prairie voles (Samuel et al, 2008). Evidence for an involvement of the CRH system in the modulation of social memory has been demonstrated by Heinrichs (2003) using CRH-R agonists and antagonists.…”
Section: The Role Of Ucn3 In Social Behaviormentioning
confidence: 99%
“…Nevertheless, it has been demonstrated that UCN1 and UCN3 modulate maternal behavior via CRH-R2 in the lateral septum D'Anna and Gammie, 2009), and accordingly, CRH-R2 knock-out mice exhibit impaired maternal defense of their offspring . Along these lines, UCN2 increases spontaneous parental behavior in prairie voles (Samuel et al, 2008). Evidence for an involvement of the CRH system in the modulation of social memory has been demonstrated by Heinrichs (2003) using CRH-R agonists and antagonists.…”
Section: The Role Of Ucn3 In Social Behaviormentioning
confidence: 99%
“…The crosstalk between parental and feeding circuits is supported by additional evidence from urocortin peptides that bind the CRF receptors, and are best known for their role in stress and appetite (Spina et al, 1996). Interestingly, urocortin II both suppresses feeding behavior in rats (Ohata and Shibasaki, 2004) and induces spontaneous parental behavior in male and female prairie voles (Microtus ochrogastor) (Samuel et al, 2008). It is clearly crucial to inhibit the eating of offspring by parents, and the link between feeding-related peptides and suppression of infanticide behavior in parental rodents warrants future research.…”
Section: Feeding-related Peptides In Rodent Parental Carementioning
confidence: 99%
“…Further, pairing with a female elicited an increase in CRF mRNA in the BNST of male prairie voles [29]. Finally, icv administration of urocortin-II, a member of the CRF peptide family, increased passive parental behavior in both male and female prairie voles, but this treatment had no effects on anxiety or locomotor behaviors [190]. …”
Section: Other Neurochemicals/hormones Implicated In Pair Bondingmentioning
confidence: 99%